Perceptions of Risk From Man-Eating Lions in Southeastern Tanzania - Kushnir, Hadas; Packer, Craig (Frontiers in Ecology and Evolution, 2019)
Perceptions of risk are a critical component of understanding the human dimensions of human-wildlife conflict as perceptions greatly affect peoples’ attitudes and behaviors towards wildlife. However, accurately assessing perceptions can be difficult since risk is often subjective and perceptions are affected by both emotions and experience. Lions attacked over 1000 people in Tanzania between 1990 and 2007. We conducted questionnaire surveys to examine multiple aspects of risk perceptions in the areas with the highest incidence of lion attacks, focusing on three general questions: (1) how villagers perceive their overall risk of attack; (2) what factors influence risk perceptions; and, (3) what aspects of risk are perceived accurately. Overall, people overestimated their risk from lions: 53% of respondents felt they are very likely to be attacked while the actual risk is estimated at less than 1% over an average lifespan. Risk perceptions were correlated with gender, age, education, acres of cultivated land and number of livestock owned but not with previous experience with lion attacks in either the village or family or with sighting of lions or lion signs. Nevertheless, people were very aware of who was at relatively high risk and when and where risks were greatest. People also accurately assessed the risk from lions compared with mega-herbivores but not compared with other predatory species or with disease and famine, emphasizing the tendency for people to overestimate risks that are rare but elicit strong fears. This study highlights the value of using interdisciplinary techniques to examine human dimensions of human-lion conflict as risk perceptions and local knowledge can identify gaps in understanding that could improve conflict-prevention programs.